2022
DOI: 10.1111/1745-9133.12613
|View full text |Cite
|
Sign up to set email alerts
|

Restorative justice programs and practices in juvenile justice: An updated systematic review and meta‐analysis for effectiveness

Abstract: Research summary: Restorative justice (RJ) in practice has taken on many different forms. It is argued that RJ does not have definitional boundaries, making it hard to limit its essence to that of a particular program, practice, philosophy, or outcome. Therefore, this study's objective was to systematically review and statistically synthesize all available research on RJ programs and related programs and practices using meta-analytic methods. Our updated systematic search and metaanalysis identified a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The volunteers’ role within restorative justice is often overlooked within the literature (Paul and Borton, 2013) and time constraints can add additional barriers to a hard-to-reach population. The effectiveness of restorative justice is often considered in terms of a reduction of the victim in the negative impacts of crime (Lloyd and Borrill, 2020) and a reduction in recidivism rates for the offender (Kennedy et al , 2019; Kimbrell et al , 2022). However, there is much to be learned from the volunteers who also play a vital role in this type of community justice.…”
Section: Further Discussionmentioning
confidence: 99%
“…The volunteers’ role within restorative justice is often overlooked within the literature (Paul and Borton, 2013) and time constraints can add additional barriers to a hard-to-reach population. The effectiveness of restorative justice is often considered in terms of a reduction of the victim in the negative impacts of crime (Lloyd and Borrill, 2020) and a reduction in recidivism rates for the offender (Kennedy et al , 2019; Kimbrell et al , 2022). However, there is much to be learned from the volunteers who also play a vital role in this type of community justice.…”
Section: Further Discussionmentioning
confidence: 99%
“…Powell et al (2021) and Yunin et al (2022) argue that such programmes' effectiveness depends on the interaction between judicial authorities, social services and educational institutions. Kimbrell et al (2023) emphasise that educational programmes and professional training courses integrated into judicial practice can significantly contribute to social adaptation and reduce the risk of recidivism. The importance of this aspect in the context of humane justice cannot be overestimated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent review of reviews (Gaffney et al, 2022) identified the most recent and relevant systematic reviews (i.e., Kimbrell et al, 2022;Latimer et al, 2005;Livingstone et al, 2013;Strang et al, 2013;Wilson et al, 2017;Wong et al, 2016). The conclusion of this overview of reviews was that overall RJ interventions have a desirable impact on offending and reoffending rates in children and young people.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…Wilson et al (2017) conducted an extensive systematic review and meta-analysis of evaluations of restorative justice with children and young people, across a diverse range of programmes. Kimbrell et al (2022) have since updated this review, and found a desirable overall impact of restorative justice on future delinquent behaviour (g = 0.23, 95% confidence interval [CI]: 0.14, 0.32). Searches for this review were conducted up to November/ December 2020 (Kimbrell et al, 2022) and so our proposed searches will further update earlier findings by searching for the most recent evaluations.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%